U.S. parents' attitudes toward playful learning - Wright, Charlotte Anne; Pasek, Josh; Lee, Ji Young; Masters, Ally S.; Golinkoff, Roberta Michnick; Thomsen, Bo Stjerne; Hirsh-Pasek, Kathy (Frontiers in Developmental Psychology, 2023)
Introduction There has been a surge of research on the power of play to facilitate learning in recent years. Guided play, specifically, has emerged as an optimal learning approach over free play and direct instruction. However, whether parents' attitudes toward play align with the emerging research remains largely unexplored. Addressing this gap, the present study is the first to operationalize play by using the playful learning spectrum (i.e., free play, guided play, games, and direct instruction) to investigate parents' attitudes toward play. Methods The study surveyed a broad, national sample of parents with at least one child aged 2 to 12 years living in the United States (N = 1,172). To understand preferences for each approach and the factors related to those preferences, we examined how individuals regarded each of the four learning approaches and ran a series of regressions predicting perceptions of learning from the approaches as a function of demographic and attitudinal factors. These regressions were estimated in two different ways, allowing us to identify which predictors were related to each outcome as well as which explained these perceptions uniquely, over and above other predictors. Results The findings revealed a preference for play over direct instruction, with parents likely to perceive free play as most conducive to learning. Regression analyses uncovered significant variations in perceptions based on demographic and attitudinal factors, with highly educated respondents most likely to endorse free play, more knowledgeable respondents most likely to endorse guided play and the least educated respondents most likely to favor direct instruction. Discussion While the study reveals parents' evolving, positive attitudes toward play, it also underscores a gap between academic research, which highlights the advantages of guided play, and parents' perceptions. Implications for parent support initiatives are discussed.